Perubahan Keluhan Seksual (Fisik dan Psikologis) pada Perempuan Pascaterapi Kanker Serviks Setelah Intervensi Keperawatan - Afi yanti; Andrijono Andrijono; Gayatri Gayatri (Universitas Airlangga, 2011)
Introduction: Despite increasing awareness related to sexual health for cervical cancer survivors, health care providers are passive in addressing their sexual issues. The objectives were to develop and investigate the effect of a sexual nursing intervention packet to mitigate sexual dysfunction among cervical cancer survivors.Methods: A sample of 104 survivors were participated consecutively based on required inclusive criteria in this quasi-experimental study. The sexual nursing intervention packet focused on the physical, psychological, and care of relational aspects of sexual health elements. The packet consisted of 6 weekly 2-hour sessions.Results: The participants reported poor sexual satisfaction and sexual function. There were no statistically signi fi cant differences in sexual interest, sexual arousal, orgasm, and vaginal lubrication improvement following the intervention, although all the variables in the intervention group were improved clinically. The sexual nursing intervention packet was effective in increasing sexual satisfaction and decreasing dispareunia among cervical cancer survivors.Conclusion: This study suggests that the quality of life in cervical cancer survivors could be improved with the sexual nursing intervention packet provided as part of supportive group care. This program may be more effective if delivered earlier and for a longer period. Implications for Practice: The sexual nursing intervention packet offers an opportunity to facilitate small-group dynamics that lay the ground for further contacts leading to earlier recognition of sexual problems and active involvement for sexual health improvement for cervical cancer survivors and nurses. It could be utilized for survivor education or support groups to increase sexual satisfaction following cancer treatment.